Volume 7: Operations, Applications, and Components 2006
DOI: 10.1115/pvp2006-icpvt-11-93835
|View full text |Cite
|
Sign up to set email alerts
|

Corrosion Resistance of Iron-Based Amorphous Metal Coatings

Abstract: New amorphous-metal thermal-spray coatings have been developed recently that may provide a viable coating option for spent nuclear fuel & high-level waste repositories [Pang et al. 2002; Shinimiya et al. 2005; Ponnambalam et al. 2004; Branagan et al. 2000–2004]. Some Fe-based amorphous-metal formulations have been found to have corrosion resistance comparable to that of high-performance alloys such as Ni-based Alloy C-22 [Farmer et al. 2004–2006]. These materials rely on Cr, Mo and W for enhanced corrosion… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
24
0
1

Year Published

2007
2007
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(26 citation statements)
references
References 0 publications
1
24
0
1
Order By: Relevance
“…One of the most promising formulations within this family was found to be Fe 49.7 Cr 17.7 Mn 1.9 Mo 7.4 W 1.6 B 15.2 C 3.8 Si 2.4 (SAM2X5), which included chromium (Cr), molybdenum (Mo), and tungsten (W) for enhanced corrosion resistance, and boron (B) to enable glass formation and neutron absorption [11][12][13][14][15] Figure 1. These new iron-based amorphous metals have exceptional neutron absorption characteristics, and are stable at high dose.…”
Section: Introductionmentioning
confidence: 99%
“…One of the most promising formulations within this family was found to be Fe 49.7 Cr 17.7 Mn 1.9 Mo 7.4 W 1.6 B 15.2 C 3.8 Si 2.4 (SAM2X5), which included chromium (Cr), molybdenum (Mo), and tungsten (W) for enhanced corrosion resistance, and boron (B) to enable glass formation and neutron absorption [11][12][13][14][15] Figure 1. These new iron-based amorphous metals have exceptional neutron absorption characteristics, and are stable at high dose.…”
Section: Introductionmentioning
confidence: 99%
“…Several Fe-based amorphous metal formulations have been found that appear to have very good corrosion resistance, based on measurements of the passive film breakdown potential, the corrosion rate and performance during salt fog testing [8][9][10]. These formulations use chromium (Cr), molybdenum (Mo), and tungsten (W) to provide corrosion resistance, boron (B) to enable glass formation, and yttrium to lower the critical cooling rate (CRR).…”
Section: Introductionmentioning
confidence: 99%
“…One of the most promising formulations within this family was found to be Fe 49. 7 Cr 17.7 Mn 1.9 Mo 7.4 W 1.6 B 15.2 C 3.8 Si 2.4 (SAM2X5), which included chromium (Cr), molybdenum (Mo), and tungsten (W) for enhanced corrosion resistance, and boron (B) to enable glass formation and neutron absorption [11][12][13][14][15]. The parent alloy for this series of amorphous alloys, which is known as SAM40 and represented by the formula Fe 52.3 Cr 19 Mn 2 Mo 2.5 W 1.7 B 16 C 4 Si 2.5 , has less molybdenum than SAM2X5 and was originally developed by Branagan [16][17].…”
Section: Introductionmentioning
confidence: 99%